EXCLI Journal; 20:Doc1571; ISSN 1611-2156 2021
DOI: 10.17179/excli2021-3484
|View full text |Cite
|
Sign up to set email alerts
|

Toxic heavy metal concentrations in multiple sclerosis patients: a systematic review and meta-analysis

Abstract: The present meta-analysis was performed to assess the association between MS patients and control subjects in terms of their circulating levels of arsenic (As), lead (Pb), mercury (Hg), and cadmium (Cd). We searched Medline/PubMed, Scopus, Web of Science, and Embase up until June 2020 to identify all studies that examined the concentrations of heavy metals in MS patients. Statistical tests used to assess inter-study heterogeneity were Cochrane's Q test and the I 2 statistic. Given the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Apart from studies confirming a higher incidence of MS in areas where soils contain high concentrations of lead [ 7 , 34 , 35 , 36 ], there are also studies showing no such relationships [ 37 , 38 ]. The only meta-analysis conducted to date in the field of toxic heavy metal concentrations in MS patients did not show any significant differences in blood lead levels between MS patients and healthy controls [ 39 ]. Therefore, the hypothesis about higher exposure to heavy metals among MS patients living in large cities in Poland has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from studies confirming a higher incidence of MS in areas where soils contain high concentrations of lead [ 7 , 34 , 35 , 36 ], there are also studies showing no such relationships [ 37 , 38 ]. The only meta-analysis conducted to date in the field of toxic heavy metal concentrations in MS patients did not show any significant differences in blood lead levels between MS patients and healthy controls [ 39 ]. Therefore, the hypothesis about higher exposure to heavy metals among MS patients living in large cities in Poland has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MS, the role of TMs and of particulates and gaseous pollutants present in the air as putative triggers of both the development and relapse of MS has been shown [ 10 ]. Moreover, patients with MS have significantly higher levels of circulating As and Cd compared to controls [ 11 ].…”
Section: Toxic Metals As Risk Factors For Ndmentioning
confidence: 99%
“…6 Although the pathogenesis of MS remains to be fully understood, 7 this disease is associated mainly with complex interactions between genetic and environmental factors. 8,9 Linked to the "hygiene hypothesis," it has been speculated that infection with particular microorganisms, particularly those occurring in childhood, may have a protective effect against allergic and autoimmune diseases. 10 In this regard, several studies have examined the possible involvement of infectious agents, such as Epstein-Barr virus and Toxocara spp., in promoting MS development, 8,[11][12][13] and others have suggested that parasites (e.g., Toxoplasma gondii, Necator americanus, and Trichuris suis) might prevent MS. [14][15][16] There is also been considerable debate as to whether Helicobacter pylori (H. pylori) is involved in development of MS or not.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the various treatment strategies presently used, such as interferon (a drug in the disease‐modifying therapies class) prescription for inhibiting disease progression, faster diminishing of attacks, and reducing the bothersome symptoms of MS, 5 current therapeutic options for the treatment of MS remain inadequate 6 . Although the pathogenesis of MS remains to be fully understood, 7 this disease is associated mainly with complex interactions between genetic and environmental factors 8,9 . Linked to the “hygiene hypothesis,” it has been speculated that infection with particular microorganisms, particularly those occurring in childhood, may have a protective effect against allergic and autoimmune diseases 10 .…”
Section: Introductionmentioning
confidence: 99%